UMP study showed Bank Rakyat Foundation offered the best education financial aids - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) carried out a study on ‘Competitive Analysis of Selected Successful Corporate Foundations in Malaysia’ involving four corporate foundations and found out that Bank Rakyat Foundation (YBR) was the best in providing education aids to the highly potentials and less privileged. The study was made based on competitiveness and contributions towards human capital in education management.